2016
DOI: 10.1177/1367493515598644
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, and quality of life in Iranian mothers of children with autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is being more recognized and diagnosed in developing as well as developed countries. We aimed to investigate the frequency of anxiety, depression, and quality of life in mothers of children with ASD in Iranian families. We conducted a descriptive cross-sectional study on demographic data and mental health characteristics of 127 mothers of children with ASD. Mothers of children with ASD had high levels of anxiety (72.4%), depression (49.6%), and low scores of health-related qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
29
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 30 publications
7
29
0
8
Order By: Relevance
“…Most previous studies in Iran have explored QOL in mothers of autistic children, while ignoring the fathers (11,12). Therefore, in the present study, we examined a hypothesis, suggesting a significant difference in HRQOL of mothers and fathers of autistic children.…”
Section: Introductionmentioning
confidence: 93%
“…Most previous studies in Iran have explored QOL in mothers of autistic children, while ignoring the fathers (11,12). Therefore, in the present study, we examined a hypothesis, suggesting a significant difference in HRQOL of mothers and fathers of autistic children.…”
Section: Introductionmentioning
confidence: 93%
“…Accordingly, many researchers have designed and conducted studies on this matter. Studies on the quality of life in the mothers of children with an autism disorder, 17,18 the mothers of children with cerebral palsy, 19 and the mothers of mentally disabled children 20 are among the examples in this regard. The stresses and problems that the mothers of these children experience may affect their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that the sources of stress experienced by mothers who have children with special needs can be categorized as internal and external factors. The internal factors include: 1) mother's perception of her child's condition [12]; 2) mothers' negative feelings such as depression [13]; anxiety [14,15]; doubt of her child's future [16]; 3) strength in coping with stress sources [17]; 4) negative public stigma of child with special need [18 -21], which generates shame of having child with special need [22]; 5) personality [23]; hardiness is a personality character, which consists of a set of attitudes resulting in strength in coping with stressing life events [24]; 6) Individual's personal resources [25]. The external factors include: 1) low social support to mothers of children with special needs [26]; 2) children's limitedness such as children's dependence on parents [27], low capability of communicating their requests [28], increasing maladaptive behaviors of children [29 -32]; incapability of controlling their emotions [33]; 3) high cost of fulfilling children's needs [34].…”
Section: Introductionmentioning
confidence: 99%